2020
DOI: 10.1177/1087054720978553
|View full text |Cite
|
Sign up to set email alerts
|

Birds of a Feather: An Examination of ADHD Symptoms and Associated Concerns in Partners of Adults with ADHD

Abstract: Objective: Adults often select romantic partners who behave like they do (i.e. assortative mating). However, little is known about whether assortative mating is common among adults with attention-deficit/hyperactivity disorder (ADHD) and whether it is related to associated problems. Method: About 94 adults without ADHD, 43 adults with childhood ADHD histories but without current symptoms or impairment (ADHD-Desist), 27 adults with childhood ADHD histories and elevated current symptoms and impairment (ADHD-Pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Still, the Wymbs and Molina (2015) sample was treatment seeking, and results—including rates of shared ADHD symptoms—may not generalize to couples not participating in therapy. In a subsequent study of an online, community sample, Steele et al (2020) found adults diagnosed with ADHD in childhood, especially those with elevated current symptoms, reported that their partners had more clinically significant symptoms of ADHD than adults without ADHD histories. Notably, the adults with persistent ADHD who had partners with elevated ADHD symptoms also tended to report more psychological and physical IPV perpetration and victimization than adults without ADHD histories, even among those with partners exhibiting elevated ADHD symptoms.…”
Section: Predictors Of Romantic Relationship Quality Among Adults With Adhdmentioning
confidence: 99%
“…Still, the Wymbs and Molina (2015) sample was treatment seeking, and results—including rates of shared ADHD symptoms—may not generalize to couples not participating in therapy. In a subsequent study of an online, community sample, Steele et al (2020) found adults diagnosed with ADHD in childhood, especially those with elevated current symptoms, reported that their partners had more clinically significant symptoms of ADHD than adults without ADHD histories. Notably, the adults with persistent ADHD who had partners with elevated ADHD symptoms also tended to report more psychological and physical IPV perpetration and victimization than adults without ADHD histories, even among those with partners exhibiting elevated ADHD symptoms.…”
Section: Predictors Of Romantic Relationship Quality Among Adults With Adhdmentioning
confidence: 99%
“…The high proportion of elevated clinical ADHD symptoms among their participants suggests that adults with ADHD tend to choose partners who also have elevated levels of ADHD symptoms at a much higher rate than would be expected by chance alone. Steele conducted research on adults diagnosed with childhood ADHD, especially those who are currently symptomatic, have partners who, compared to adults with no history of ADHD had more pronounced clinical symptoms of ADHD [51]. Differences in like-mating rates between adults with persistent ADHD and adults with indifferent ADHD were also assessed, and the results indicated that adults in the persistent ADHD group (ADHD-Persist) were more likely to choose partners with exacerbated ADHD symptoms than adults in the ADHD-indifferent group (ADHD-Desist), thus extending previous research efforts.…”
Section: Mediating Effects Of Co-morbiditiesmentioning
confidence: 99%